ANALISIS PERHITUNGAN LINK BUDGET INDOOR ENETRATION WIDEBAND CODE DIVISION MULTIPLE ACCESS (WCDMA) DAN HIGH SPEED DOWNLINK PACKET ACCESS (HSDPA) PADA AREA PONDOK INDAH - Surjati, Indra; Ningsih, Yuli Kurnia; Septiana, Hendri (Jurnal Teknik Elektro, 2008)
The indoor penetration manifested as macro cell system which is the extension of outdoorsignalling into indoor premises, can be implemented both by High Speed Downlink PacketAccess (HSDPA) and Wideband Code Division Multiple Access (WCDMA) as well in thearea of 3.5G related application. The significant parameters being used in this researchwere Effective Isotropic Radiated Power (EIRP) and Received Signal Code Power (RSCP).The results showed that for data down linking operation the EIRP 58 dBm and the RSCP -69.94 dBm for WCDMA, while the EIRP 56 dBm and the RSCP -71.64 dBm for HSDPA.Furthermore, the drive test results showed for HSDPA running File Transfer Protocol (FTP)application the RSCP -92.2 dBm with throughput â2,0Mbps, while for running Hyper TextTransfer Protocol (HTTP) application the RSCP -95 dBm with throughput â1.9Mbps. Thedrive test result for WCDMA showed the RSCP is -69.72 dBm with throughput 328 kbps.Keywords: High Speed Downlink Packet Access (HSDPA), Wideband Code DivisionMultiple Access (WCDMA), Hyper Text Transfer Protocol (HTTP), FileTransfer Protocol (FTP)